Intermediate Algebra (6th Edition)

Published by Pearson
ISBN 10: 0321785045
ISBN 13: 978-0-32178-504-6

Chapter 5 - Review: 112

Answer

(x - 7)(x + 1)

Work Step by Step

$(x - 3)^{2}$ - 16 = $x^{2}$ - 6x + 9 - 16 = $x^{2}$ - 6x - 7 = (x - 7)(x + 1) Check by multiplying factors with FOIL: x(x) + x(1) - 7(x) - 7(1) = $x^{2}$ + x - 7x - 7 = $x^{2}$ - 6x - 7
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.